Heterogeneity in endothelial cells and widespread venous arterialization during early vascular development in mammals - Hou, Siyuan; Li, Zongcheng; Dong, Ji; Gao, Yun; Chang, Zhilin; Ding, Xiaochen; Li, Shuaili; Li, Yunqiao; Zeng, Yang; Xin, Qian; Wang, Baihan; Ni, Yanli; et al. (Cell research, 2022)
Arteriogenesis rather than unspecialized capillary expansion is critical for restoring effective circulation to compromised tissues in patients. Deciphering the origin and specification of arterial endothelial cells during embryonic development will shed light on the understanding of adult arteriogenesis. However, during early embryonic angiogenesis, the process of endothelial diversification and molecular events underlying arteriovenous fate settling remain largely unresolved in mammals. Here, we constructed the single-cell transcriptomic landscape of vascular endothelial cells (VECs) during the time window for the occurrence of key vasculogenic and angiogenic events in both mouse and human embryos. We uncovered two distinct arterial VEC types, the major artery VECs and arterial plexus VECs, and unexpectedly divergent arteriovenous characteristics among VECs that are located in morphologically undistinguishable vascular plexus intra-embryonically. Using computational prediction and further lineage tracing of venous-featured VECs with a newly developed Nr2f2 CrexER mouse model and a dual recombinase-mediated intersectional genetic approach, we revealed early and widespread arterialization from the capillaries with considerable venous characteristics. Altogether, our findings provide unprecedented and comprehensive details of endothelial heterogeneity and lineage relationships at early angiogenesis stages, and establish a new model regarding the arteriogenesis behaviors of early intra-embryonic vasculatures.